The Historiography of Accounting: Diponegoro [Lease & Tax] Accountability - Faizah Kusuma Wardhani; Resi Ariyasa Qadri; Aldilla Yasmin Inas (Jurnalku, 2022)
This study aims to examine lease accounting and taxation in the Sultanate of Yogyakarta during the Diponegoro era, lessons acquired through conflicts over these occurrences, and their significance with lease accounting standards (PSAK 73). This qualitative research uses history books, e-journals, accounting standards, and videos about Sultanate of Yogyakarta. This study reveals that land leasing and taxation practices during the period lacked internal and external accountability. Some events in the Sultanate of Yogyakarta during that time are pertinent to current events reviewed using PSAK 73, such as the relationship between Zimbabwe and China and the experience of Indonesian tenant farmers. Accounting, tax, and agrarian policymakers need field research with enough samples to improve policy implementation.